Tuning the composition of BixWyO nanorods towards zero bias PEC water splitting. (16th May 2016) - Larson, Steven; Zhao, Yiping
Abstract: A unique co-oblique angle deposition method was used to create nanorod arrays of mixed phase Bi2 O3 /WO3 /Bi2 WO6 with varying atomic ratios of Bi to W. The effect of the tuning on the resulting nanostructures was characterized by EDX, SEM, XRD, optical transmission, specular reflection, and diffuse reflection spectroscopy. Samples with different Bi:W atomic ratio had a wide range of morphology and composition due to the surface mobility of deposited bismuth and its volume expansion during oxidation. Their photocatalytic and photoelectrochemical properties were investigated by methylene blue degradation and photo-generated current respectively. The sample with 38 at.% Bi showed the highest photodecay rates as well as the maximum photocurrent density, 4.3 μ A cm −2, at a bias potential of 600 mV versus Ag/AgCl (3M KCl); while the sample with 50 at.% Bi exhibited a high photocurrent density of 0.35 μ A cm −2 at zero bias potential, which indicates that varying the composition and mixed crystal phases of different oxides with appropriate band gaps and locations could hold the key to a visible light driven, zero bias potential, photoelectrochemical cell.